Civil Religion di Indonesia - Parmudi, Mochamad (JSW (Jurnal Sosiologi Walisongo), 2018)
Indonesia is a democracy. Therefore the government must encourage and guarantee freedom of speech, religion, opinion, an association for every citizen. The government must enforce the rule of law which the majority must respect the rights of minority groups and their citizens give each other equal opportunities to live together to get a decent life. The Republic of Indonesia is a unitary state with a high degree of plurality in the fields of religion, ethnicity, race, and class. To support religious life, the national and state community in a peaceful, healthy, prosperous and happy manner, civil religion is needed. This research is a phenomenological study focusing on analyzing the description and explanation of civil religion in Indonesia. A phenomenological approach is used in interpreting the "meaning" of data. With this method, it is expected to obtain interpretations about civil religion in Indonesia. The results of this study concluded that Pancasila could become a "civil religion in Indonesia", at least it had developed along with the will of the people who led, and placed Pancasila as a transcendental backing (civil religion). Pancasila with its five principles is a real picture of civil religion.